Factors Influencing FinTech Adoption Behavior of Millennials in Nepal: Evidence from Karnali Province, Nepal (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to investigate the factors affecting FinTech adoption intention among millennials in the Karnali Province, Nepal.Methods: A descriptive and causal-comparative research design was employed in this study. A total of 410 samples were collected using the purposive sampling technique. Data were collected through structured questionnaires administered physically and online and analyzed using structural equation modeling to estimate the relationships between the observed variables and latent constructs.Results: The findings of this study reveal that digital literacy (DL), trust in technology (TT), perceived ease of use (PEU), and social influence (SI) emerged to be the critical determinants affecting the fintech adoption behavior of millennials. The results show significant effects of DL, TT, PEU, and SI on FinTech Adoption Intention (FAI).Conclusion: The findings suggest that creating awareness surrounding digital capabilities, instilling positive trust and faith in the technological systems, making the user interface of financial platforms more approachable and implementing social influence could improve the adoption of FinTech solutions in Nepal.